THE TURN OF THE “BAD FEMINIST”: PROBING MONSTROSITY IN THE SHARED UNIVERSE OF THE HANDMAID’S TALE - Copati, Guilherme (Abusões, 2022)
This essay aims at tentatively probing the figure of the “bad feminist” in the shared universe of The Handmaid’s Tale, composed as it is by Hulu’s adaptation of Margaret Atwood’s homonymous 1985 novel and the Canadian author’s 2019 sequel, The Testaments. After briefly examining the figure of the “bad feminist” in the context of the fourth wave of feminism, we offer notes on how the characters of June Osborne in Hulu’s series and Aunt Lydia in The Testaments may have been rendered monstrous bad feminists for their rejection of norms of solidarity, a constitutive and dominant tenet of fourth-wave feminism, seeing how the monster could be described as the embodiment of the anti-norm which renders normatvie social configurations visible and stable.